A 39-Year-Old Woman with Oculodermal Melanocytosis: A Case Report - Fensilia Yolanda, Gina Sonia; Ramzi Amin; H. A. K. Ansyori (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2024)
Introduction: Nevus of Ota, also known as oculodermal melanocytosis (ODM), is characterized by macular pigmentation which localized to the forehead and periocular area. It usually shows a dermatomal distribution from the first two branches of the trigeminal nerve. We reported a case of oculodermal melanocytosis (ODM). Case presentation: A 39-year-old woman, came with complaints of her left eye rolling inwards for the past 5 years accompanied by a flat black spot on her forehead that spread to her left cheek. She was done macular OCT and orbital ultrasonography of the left eye. She was diagnosed with oculodermal melanocytosis in the left eye, moderate NPDR in both eyes, juvenile cataracts in both eyes, and esotropia in the left eye due to left-eye cranial nerve VI paralysis. Follow-up at 6 months was advised to the patient. Conclusion: Although this is a benign condition, patients are at risk of developing complications such as increased intraocular pressure and melanoma of the skin and/or uvea, ongoing evaluation with imaging methods is highly recommended even if only skin lesions may be repaired using laser for cosmetic reasons.